Antenna‐based solutions for RF probes in ultra high field magnetic resonance imaging scanners. Issue 12 (19th October 2018) - Gandji, Navid P.; Semouchkin, George; Semouchkina, Elena
Abstract: Various approaches to designing unconventional antenna‐based RF probes for obtaining homogeneous 600 MHz B1 magnetic field in 14 T MRI scanners are investigated. Proposed solutions include microstrip patch antennas with engineered multidielectric substrates, acting as surface coils, and systems of vis‐à‐vis placed patch antennas to be used as volume coils with essentially increased Q‐factors compared to those of birdcage coils. Various options of controlling magnetic near fields in antenna systems with flat, cylindrical and cosine‐shaped substrates, as well as with tapered patch electrodes, are demonstrated. Problems of fabricating unconventional microstrip patch antennas for MRI applications are also addressed.